2017
DOI: 10.12669/pjms.331.11222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender and Physical Activity on Internet Addiction in Medical Students

Abstract: Objective:To determine the effect of gender and physical activity on internet addiction in medical students.Methods:In this cross sectional, analytical study Young’s internet addiction test questionnaire was distributed to 350 MBBS students of Army Medical College, Rawalpindi. The study was conducted from January to May 2015. A dichotomous response from students regarding physical activity was obtained which was verified from the sports department of the institution. Based upon total score, internet addiction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
45
3
8

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 13 publications
10
45
3
8
Order By: Relevance
“…The proportion of students with PIU was slightly higher among female students, though the difference was not significant (Tables , and S1), which is consistent with some previous studies in Japan . It is possible that differences in students’ Internet activities may be related to sex, which would lead to sex differences in the prevalence of PIU, though no conclusions have been reported . In our research, the proportion of students who played games was high among boys, whereas the proportion of those who used the LINE application was high among girls (Table ), which is consistent with the trend reported in previous studies .…”
Section: Discussionsupporting
confidence: 90%
“…The proportion of students with PIU was slightly higher among female students, though the difference was not significant (Tables , and S1), which is consistent with some previous studies in Japan . It is possible that differences in students’ Internet activities may be related to sex, which would lead to sex differences in the prevalence of PIU, though no conclusions have been reported . In our research, the proportion of students who played games was high among boys, whereas the proportion of those who used the LINE application was high among girls (Table ), which is consistent with the trend reported in previous studies .…”
Section: Discussionsupporting
confidence: 90%
“…[10] Preference for mobile might be because of portability of the device and recent development in features. Both boys and girls preferred to browse in the night, and the main accessed website reported among UG students were Google followed by Yahoo which was quite similar to the findings of Neeraj and Swarupa [11] The appliances chosen, preferences and reasons for the use of internet services did not differ much among gender which is quite similar to the observations of Thanuskodi and Khan et al and also Anasi and Owoeye [12][13][14] though earlier studies by Chen et al [15] and many others suggested gender gap. Similarities in use may be probably because both genders have high exposure to the technology through their educational experience to realize their capabilities and reach the full potentials most of the students were aware of recent applications and were using the same for both academic and entertainment purpose which shows the awareness about recent developments in the information technology world supporting the findings of Pujazon-Zazik and Park who concluded that girls and boys have relatively equal interest in computers use the internet differently for different purposes.…”
Section: Discussionsupporting
confidence: 85%
“…Ekinci et al (2016), mentioned a positive relationship between regular sports participation and game addiction. According to the study of Khan et al (2017), "total score and frequency of internet addiction were higher in students lacking physical activity as compared to those with regular physical activity". According to Danish et al (1995) and Pitter & Andrews (1997), sports activities have regarded as a handy tool to prevent a variety of social issues.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly addictions on the internet are online gaming, social networking and online shopping (Khan et al 2017). In the recent years, researches have been conducted to answer the question "whether technological addictions such as internet addiction, social media addiction, digital game addiction and smartphone addiction are myths or are they behavioral addictions?"…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation